ترميم المسجد العتيق سيدي مسعود بمدينة الوادي - خامسة, عمار (Laghouat : Université Amar Telidji - Département d'architecture, 2022)
The city of Oued Souf has many archaeological monuments with an architectural character specific to the region that you cannot find in other places. Among the most important of these historical monuments are the mosques that are widely spread within the antique neighborhoods to owe the people of the Souf region. Cultural and heritage, which is the subject of our study. After the teacher's diagnosis, we found the mosque's condition deteriorating due to many damage factors, the most important of which are: the erosion and subsidence of the foundations, the bearing walls, due to water leakage. We aim to protect the building from collapse and damage by restoring it by proposing different solutions in the intervention project using local building materials and modern techniques, the most important of which are: placing tie rods between the arches and strengthening the structural structure of the mosque.
Restauration de la mosquée El-Atik Sidi Messaoud de la ville d’El-Oued